RANCANG BANGUN ROBOT KRI 2012 - Andreas Hadi; Agus Halim; Noor Eddy (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: Designing Robot KRI 2012 is applied in the industrial world that serves as a means of shifting materials. At KRI 2012 the game that took the motto "Peng on Dai Gat" and the theme "In Pursuit of Peace and Prosperity". Robot designed KRI 2012 which is the type of manual robot that has some tasks that take up, lift, and insert tokens into the token box, lift the basket, also the collector robot design will discuss base design such as determined DC motors, lifting, minimum pressure on the gripper token, the determine of PWM DC motor, slope and deflection that occurs on the rod lifter. So in designing this robot should also be able to support the weight of the operator who will be driving this robot. The method used is to use a simple calculation of the literature used to obtain data on the results of the design and use test with tachometer to get the motor and calculate the mileage time of the robot at 6 m. Then the data will be used as input to obtain design models robot KRI 2012 on Autodesk Inventor 2012.